Magic Tree House #22 : Revolutionary War on Wednesday - Mary Pope Osborne (Random House USA Children's Books New York, 2002)
Jack and Annie are ready for their next fantasy adventure in the bestselling middle-grade series--the Magic Tree House! It is a dark and snowy night when the Magic Tree House whisks Jack and Annie back to colonial times. General George Washington is about to lead his army in a sneak attack against their enemy. But now a terrible weather is making the great general question his plans. Can Jack and Annie keep history on track? The fate of the country rests in their hands! Visit the Magic Tree House website! MagicTreeHouse.com
Keywords: Historical Fiction -- Historical Fiction